Ectoparasites on freshwater fishes (Clarias gariepinus and Oreochromis niloticus) in fish farm at Kiambalang, Inanam / Neneyyeni Fadilis - Fadilis, Neneyyeni (2020)
The study of ectoparasites on freshwater fishes (Clarias gariepinus and Oreochromis niloticus) was carried out on June 2019 until December 2019 in fish farm at Kiambalang, Inanam. The identification, prevalence and intensity of ectoparasites on Clarias gariepinus and Oreochromis niloticus were examined in this study. A total of 45 Clarias gariepinus fish and 45 Oreochromis niloticus fish were taken from the fish farm located at Kiambalang, Inanam. The method that used was the fish sex identification, mucous scrapping, preservation of mucous, examined and identification of ectoparasites and physicochemical parameters measurement. Four species of ectoparasites were determined from both freshwater fish namely, Gyrodactylus salaris (42.22 %), Contracaecum rudolphii (24.44 %), Criconemoides morgense (46.67 %) and Caenorhabditis elegans (26.67 %). The statistical methods that used were Mann Whitney U Test for comparison and Spearman’s Rho Correlation for correlation. There were statistically significant differences (p < 0.05) between prevalence of ectoparasites and the males and females for both freshwater fish. In Clarias gariepinus, male show high prevalence compared to female which was (75.00 %), while in Oreochromis niloticus, female show high prevalence compared to male which was (75.00 %). Analysis of physicochemical parameter (pH, salinity, dissolved oxygen and temperature) were important in this study because it affecting the parasite infestation. These physicochemical parameters affect the prevalence of ectoparasites due to several factors such as tolerance of the parasite towards the physicochemical parameters, stocking density of fish, influence of the rain, and low level of water.